PERANAN CIVIL SOCIETY DALAM PENGURANGAN SAMPAH DI KOTA PEMATANG SIANTAR - Tarigan, Ivana Veronica; Sinaga, Rudi Salam; Lubis, Khairunnisah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The background of the problem is that waste is a material that is used, not used, not liked, or something that is thrown away comes from human activities. Manage is a non-governmental organization that solves waste problems without causing damage or polluting the environment by using the Black Soldier Fly (BSF). This study aims to determine the extent of the role of civil society in reducing waste and the inhibiting factors in reducing waste in Pematangsiantar City. This study uses qualitative methods, solved through observations, interviews, and documentation describing the situation based on facts with informants consisting of six people. This study uses the theory of Soerjono Soekanto (1987) there are 3 variables. Based on the results of observations and interviews, the researchers obtained the result that Manage can be said to be a civil society because it contributed to the success of a policy carried out by the government in reducing waste using the Black Soldier Fly (BSF). Manage succeeded in reducing waste in Pematang Siantar City by 21.3 tons in 7 months by utilizing increasingly sophisticated technology by providing services to the community with education and understanding as a means of information and communication. It is hoped that the government will be more concerned about providing assistance in the form of facilities and infrastructure to support the success of managing to reduce waste